Impact of Malocclusion on children studying in Government High Schools in Mardan: Impact of Malocclusion on Children - Qazi, Noor ul Ain; Gul, Hafsa; Ali Shah, Syed Wasif; Salman Khan, Muhammad; Afridi, Uzma; Falak, Nazish (Pakistan Journal of Health Sciences, 2023)
The facial looks have an impact on self-esteem and emotional well-being, playing an important role in social interactions. Changing in these functions will therefore affect the standard of living of children. Objective: The purpose of the study was to evaluate the effect of malocclusion on psychological well-being on school going children using the OASIS aged between 13-17 years attending government high schools in Mardan District. Methods: This was a Descriptive Cross-Sectional Survey conducted at the government schools of Mardan. It was carried out within a period of six month from December, 2021 till May 2022 after consent from Institutional Review Board (IRB) of Bacha Khan Medical College, Mardan vide No. 39/2021/ERB. The sample was chosen using a random cluster sampling technique with probability related to size. The design effect was taken into account as the cluster sampling approach was applied, and a sample size of 850 was achieved. (600 boys and 250 girl participants were involved respectively from government high schools). Results: A total of 850 subjects were included in the study of which there were 600 (70%) males and 250 (30%) were females. The age range was 13-17 years with a mean age 15 years +1.37 (S.D) years. Conclusions: Angle’s malocclusion was established in 73.1% of the subjects. The least affected psychologically was normal occlusion with (100%) good psychological well-being followed by Angle’s class I malocclusion having good psychological well-being (76.8%).